English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

( ^ = to the power of )

1. 3x^3 y^4 z^-2
----------------------
6x^-1 y^3 z^-3

2. 2^2
--------------
(3/2) ^-2 hint: ( 3/2 means 3 over 2 )

3. (4y)^7
--------------
(4y)^3

4. (2x^5)^3 (-3x^4)^3

5. 7(x^4)^5 (-4x^2)^2

6. ( 4x^3 )^3 hint: (parentheses mean the the whole equation ^3)
( ------ )
( 2y^2 )

7. ( 5x^3 )^2
-----------------
( 5xy^2 )^3


For questions 14 and 15, help me simplify the rational expressions.

14. -x^2 + 10x - 21
-----------------------------
-x^2 +23x - 14

15. 28x^2 - 29^x + 6
-----------------------------
- 28x^2 + 50x - 12

2006-10-28 22:46:16 · 6 answers · asked by pmgstudios 1 in Science & Mathematics Mathematics

6 answers

Hi Dear ;
{ (a ^ n ) * ( a ^ m ) = a ^ ( n + m )
(a ^ n ) / ( a ^ m ) = a ^ ( n - m )
a ^ -n = 1 / a ^ n } ....

■ Part 1
(3x^3 y^4 z^-2) / (6x^-1 y^3 z^-3) =
[ 3 / 6 ] * [ x ^3 / 6 x^ -1 ] * [ y ^ 4 / y ^ 3 ] * [ z ^ -2 / z ^ - 3 ] =
1/2 * [ x ^ 3 - (-1) ] * [ y ^ ( 4 - 3) ] * [ z ( -2 - ( -3)) ] =
1/2 ( x ^4 y z )

■ Part 2
(2^2) / (3/2) ^-2 =
{ 2 ^2 = 4 , (3/2) ^-2 = (2 /3) ^ 2 = 4 / 9 } ..
4 / (4 / 9) = ( 9 * 4 ) / 4 { cancel 4 }
2^2 / (3/2) ^-2 = 9

■ Part 3
(4y)^7 / (4y)^3 =
[ 4 ^ 7 * y ^ 7 ] / [ 4 ^ 3 * y ^ 3 ] =
[ 4 ^ (7 - 3) ] * [ y ^ ( 7 - 3)] =
(4 ^ 4) * (y ^ 4) = 256 y ^ 4

■ Part 4
(2x^5)^3 (-3x^4)^3 =
[ (2 ^ 3) * (x ^ ( 5 * 3 )) ] * [ (- 3 ^ 3) * ( x^ ( 4 * 3 ) ] =
[8 x ^ 15] * [ -27 x ^ 12 ] =
[ 8 * -27 ] * [ x ^ (15 + 12 ) ] =
- 216 ^ 27

■ Part 5
7(x^4)^5 (-4x^2)^2 =
[ 7 * ( x ^ ( 4 * 5 )] * [ -4 ^ 2 * (x ^ 2 * 2 ) ] =
[ 7 * x ^ 20 ] * [ 16 * x ^4] =
[ 7 * 16 ] * [ x ^ (20 + 4)] =
112 x ^ 24

■ Part 6
( 4x^3 )^3 / ( 2y^2 ) =
[ (4 ^ 3) * ( x ^ ( 3 * 3) ] / 2 y ^2 =
64 x ^ 9 / 2 y ^ 2 =
(64 / 2) * (x ^ 9 / y ^ 2) =
(32 x ^ 9) / y ^ 2

■ Part 7
( 5x^3 )^2 / ( 5xy^2 )^3 =
[ (5 ^ 2) * ( x ^ ( 3 * 2)] / [ ( 5 ^3) * (x ^ 3) * ( y ^ ( 2 * 3) ]
[ 25 x ^6] / [ 125 * x ^3 * y ^ 6 ] =
[ 25 / 125 ] * [ x ^ (6 - 3)] * [ 1 / y ^ 6]
( x ^ 3) / 5 y ^ 6

■ Part 8
-x^2 + 10x - 21 -x^2 +23x - 14 =
[ -x^2 -x^2 ] + [ 10x + 23x ] + [ -21 - 14] =
- 2x ^2 + 33x - 35

■ Part 9
28x^2 - 29^x + 6 - 28x^2 + 50x - 12 =
[ 28x^2 - 28x^2 ] + [- 29x + 50x ] + [ 6 - 12 ] =
21 x - 6

Good Luck dear ♣

2006-10-28 23:38:49 · answer #1 · answered by sweetie 5 · 6 0

1. 3x^4
2 9
3 4y^4
4. -6x^15
oh. So goes the answers. You are one more of the lazy lot.

Oh my god you are the same gu(al)y again. Shame Shame!

2006-10-28 22:55:35 · answer #2 · answered by Jaaji 2 · 0 0

i like powers of two. 4^x = one million/sixty 4 2^(2x) = 2^(-6) This works because of the fact the exponents have a similar base. 2x = -6 x = -3 you ought to try this with one fewer step via doing it in powers of four, yet I desire 2.

2016-12-16 16:09:38 · answer #3 · answered by biedrzycki 3 · 0 0

Why don't you just drop the course. You've already failed it. Getting over on your teacher(s) may seem cool to you now, but all you are really doing is making yourself unemployable.

2006-10-28 23:02:52 · answer #4 · answered by Helmut 7 · 0 0

Thanks for all the hints, I have them all figured out

2006-10-28 22:54:07 · answer #5 · answered by Anonymous · 0 0

14_(-x+3)(x-7)
...........................

2006-10-29 01:08:26 · answer #6 · answered by masood v 1 · 0 0

fedest.com, questions and answers